Analisis Jumlah dan Jenis Bakteri Coccus Gram Positif pada Sisa Sampel Darah di Spuit - Arfi, Sofiyan Dwi; Kristinawati, Erna; Khusuma, Ari (Jurnal Analis Medika Biosains (JAMBS), 2022)
.Background: One of the problems in the field of health services that can increase the mortality rate is nosocomial infection. Waste containing pathogenic bacteria can serve as a medium for the spread of disease for health facility workers, sufferers and the public. One of the medical devices that have a high risk factor as an intermediary for infection is a syringe. Bacterial contamination of the syringe after use cannot be ignored. Therefore, further research is needed on waste in health facilities to determine infectious diseases caused by residual blood samples in the syringe. Research Objectives: To determine the presence of gram-positive coccus bacteria in the remaining blood sample in the syringe. Methods: This study used a descriptive observational method with a cross sectional approach to time. The sample size in this study was 14 samples with a sampling technique that is total sampling. Results: It was found that Staphylococcus aureus and Staphylococcus cohnii were found each of the 14 samples. Conclusion: There are gram-positive coccus bacteria, namely Staphylococcus cohnii and Staphylococcus aureus.